2001
DOI: 10.1021/jo010305b
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structures of the Mixed Aggregates Derived from Lithium Acetylides and a Camphor-Derived Amino Alkoxide

Abstract: Low-temperature (6)Li, (13)C, and (15)N NMR spectroscopies reveal that mixtures of lithium cyclopropylacetylide or lithium phenylacetylide (RCCLi) and a vicinal amino alkoxide derived from camphor (R*OLi) in THF/pentane afford an asymmetric (RCCLi)(3)(R*OLi) mixed tetramer and a C(2)-symmetric (RCCLi)(2)(R*OLi)(2) mixed tetramer depending on the stoichiometries. The corresponding (RCCLi)(R*OLi)(3) mixed tetramer is not observed. R*OLi-mediated additions of PhCCLi to benzaldehyde proceed with up to an 8:1 enant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…Although several asymmetric (−)-sparteine-mediated reactions have been rationalized by mechanisms involving enantioselective removal of enantiotopic protons and alkylation of the resultant “chiral” sp 3 hybridized anions, this mechanism seems unlikely in the present case as a stabilized enolate is generated from 4 and expected to adopt planar sp 2 enolate geometry. The low polarity of the solvent and ability of C 2 symmetric (−)-sparteine to coordinate the lithium counterion suggests another mechanism based on π-face selection mediated by a complex chiral amine-coordinated lithium enolate rather than a chiral base mechanism . Such an alternate reaction pathway is consistent with the observed reversal of diastereoselectivity in the aldol addition of lithium enolate of 4 in the presence of (−)-sparteine, together with induction of a consistent level of asymmetry in the product that is only weakly dependent upon the structure of the aldehyde .…”
supporting
confidence: 64%
“…Although several asymmetric (−)-sparteine-mediated reactions have been rationalized by mechanisms involving enantioselective removal of enantiotopic protons and alkylation of the resultant “chiral” sp 3 hybridized anions, this mechanism seems unlikely in the present case as a stabilized enolate is generated from 4 and expected to adopt planar sp 2 enolate geometry. The low polarity of the solvent and ability of C 2 symmetric (−)-sparteine to coordinate the lithium counterion suggests another mechanism based on π-face selection mediated by a complex chiral amine-coordinated lithium enolate rather than a chiral base mechanism . Such an alternate reaction pathway is consistent with the observed reversal of diastereoselectivity in the aldol addition of lithium enolate of 4 in the presence of (−)-sparteine, together with induction of a consistent level of asymmetry in the product that is only weakly dependent upon the structure of the aldehyde .…”
supporting
confidence: 64%
“…Experimental studies for n-BuLi, n-BuOLi, and tert-BuOLi in THF solution have been reported by McGarrity et al 1,71 The alkyl aggregates exist as a dimer/tetramer equilibrium, whereas mixed alkyl/alkoxide aggregates seem to prefer tetrameric forms. Collum and co-workers 72,73 have reported another study with related systems in which they show that symmetric 2:2 aggregates are the major product in stoichiometric solutions though nonsymmetric aggregates are detected, too. From the theoretical point of view, Pratt et al 41 have reported a study confirming the higher stability of tetramers over dimers.…”
Section: Resultsmentioning
confidence: 96%
“…-78°C. 54 Variations of the alkoxide-to-acetylide ratio revealed changes in the sense of enantioselectivity, and the highest enantioselectivity (78% ee) was observed at a ratio of 1:3.…”
Section: Biographical Sketchmentioning
confidence: 99%